Ti-Zr-Mn-Fe-Bi hydrogen storage alloy and preparation method thereof

By adding Zr, Fe and Bi elements to Ti-Mn-based hydrogen storage alloy, the element ratio and high-temperature annealing process are optimized to form a uniform phase structure, which solves the problem of large hysteresis and poor cycleability of Ti-Mn-based alloys , achieving high hydrogen storage capacity and good circulation performance.

CN119410995APending Publication Date: 2025-02-11CNOOC GAS & POWER GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411350245.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing Ti-Mn-based hydrogen storage alloys have problems of large hysteresis and poor circulation, resulting in low thermodynamic efficiency of hydrogen storage and severe micronization of the alloy during hydrogen absorption and discharge.

Method used

By adding Zr, Fe and Bi elements to the Ti-Mn-based alloy, the element ratio is optimized, and a uniform phase structure is formed by high-temperature annealing, reducing element segregation and improving stability in the hydrogen absorption/desorption process.

Benefits of technology

High hydrogen storage and good circulation performance are achieved. The hydrogen storage volume can still be maintained at 99% of the initial capacity after 2000 cycles, while reducing the hysteresis during hydrogen absorption and discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410995A_ABST
    Figure CN119410995A_ABST
Patent Text Reader

Abstract

The invention discloses a Ti-Zr-Mn-Fe-Bi hydrogen storage alloy and a preparation method thereof, and belongs to the technical field of hydrogen storage alloy materials. The general molecular formula of the Ti-Zr-Mn-Fe-Bi hydrogen storage alloy is Ti < 0.85 > Zr < 0.15 > Mn < 1.5-x-y > Fe < x > Bi < y >, x is more than 0 and less than or equal to 0.2, and y is more than 0 and less than or equal to 0.2; x and y respectively represent the atomic ratio of each element. According to the invention, the problem of large hysteresis caused by segregation of alloy elements is effectively reduced; the Bi element is large in atomic radius and high in ductility, the micro strain and plastic deformation in the hydrogen absorption / desorption process can be buffered by enlarging the size of a lattice gap, and therefore the crystal structure is stabilized, the cycle life of the alloy in the long-term hydrogen absorption / desorption process is prolonged, and the service life of the alloy in the long-term hydrogen absorption / desorption process is prolonged. The hydrogen storage capacity of the prepared hydrogen storage alloy can still be kept to be 99% of the initial capacity after 2000 cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen storage alloy materials, and in particular to a Ti-Zr-Mn-Fe-Bi hydrogen storage alloy and a preparation method thereof. Background Art

[0002] As energy shortages and environmental degradation become increasingly prominent, countries around the world have launched large-scale explorations of new energy sources in recent years. Hydrogen energy, as a clean secondary energy source, is receiving more and more attention. However, the storage and transportation technology of hydrogen has become one of the key challenges in the application of hydrogen energy. Compared with traditional high-pressure gaseous hydrogen storage and liquid hydrogen storage, alloy hydrogen storage technology is regarded as an economical and efficient hydrogen storage solution due to its high storage density, good safety and portability. Therefore, we urgently need to develop hydrogen storage alloys with high hydrogen storage capacity and excellent cycle performance. Among them, Ti-Mn-based Laves phase hydrogen storage alloys have the characteristics of large hydrogen storage capacity and excellent kinetic properties, and have become a research hotspot for practical hydrogen storage alloys.

[0003] However, Ti-Mn-based hydrogen storage alloys generally have the disadvantage of large hysteresis in hydrogen absorption and desorption, which means low thermodynamic efficiency of hydrogen absorption and desorption, which brings inconvenience to the actual use process. At the same time, Ti-Mn-based hydrogen storage alloys have a serious tendency to micronize during the process of hydrogen absorption and desorption. After only a few cycles of hydrogen absorption and desorption, the alloy will be pulverized into micron-sized particles, resulting in a sharp decrease in cyclability. Shahrouz et al. studied the cyclic characteristics of Ti-Mn-V-Zr-Cr-Fe-Ni high entropy alloys, in which Ti 30 V 15.8 Mn 49.4 Zr 0.5 Cr 1.1 Fe 2.9 The alloy has good hydrogen storage properties, but after 1000 cycles its performance has been reduced to 89% of the initial capacity, and there are still potential problems in practical use. Summary of the invention

[0004] In view of the problems of large hysteresis and poor cyclability of existing Ti-Mn based hydrogen storage alloys, the present invention provides a Ti-Zr-Mn-Fe-Bi hydrogen storage alloy and a preparation method thereof.

[0005] The present invention first provides a Ti-Zr-Mn-Fe-Bi hydrogen storage alloy, the molecular formula of which is Ti 0.85 Zr 0.15 Mn 1.5-x-y Fe x Bi y, where 0<x≤0.2, 0<y≤0.2; x and y represent the atomic ratio of Fe and Bi elements respectively, that is, the ratio of the number of atoms of Fe and Bi elements in the alloy to the total number of atoms in the Ti-Zr-Mn-Fe-Bi hydrogen storage alloy.

[0006] The subscripts 0.85, 0.15 and 1.5-xy of Ti, Zr and Mn are the atomic ratios of Ti, Zr and Mn respectively, which mean the ratio of the number of atoms of Ti, Zr and Mn in the alloy to the total number of atoms in the Ti-Zr-Mn-Fe-Bi hydrogen storage alloy.

[0007] Specifically, the molecular formula of the Ti-Zr-Mn-Fe-Bi hydrogen storage alloy is any one of the following: Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.1 Bi 0.1 、Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.15 Bi 0.05 、Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.05 Bi 0.15 、Ti 0.85 Zr 0.15 Mn 1.4 Fe 0.05 Bi 0.05 .

[0008] Furthermore, the present invention provides a method for preparing the above Ti-Zr-Mn-Fe-Bi hydrogen storage alloy, comprising the following steps:

[0009] (1) preparing Ti, Zr, Mn, Fe and Bi raw materials according to the molecular formula of the Ti-Zr-Mn-Fe-Bi hydrogen storage alloy;

[0010] (2) melting and keeping the mixture in an inert atmosphere, then remelting, and obtaining an alloy ingot after repeated smelting;

[0011] (3) Annealing the alloy ingot obtained in step (2) in an inert atmosphere to obtain the Ti—Zr—Mn—Fe—Bi hydrogen storage alloy.

[0012] In the above-mentioned preparation method, in step (2), the temperature of the melting and heat preservation is 1700-1900° C.;

[0013] The melting and heat preservation time is 3 to 5 minutes;

[0014] The number of repeated smelting is 3 to 5 times.

[0015] In the above-mentioned preparation method, in step (3), the annealing temperature is 1000-1200° C.; and the annealing time is 24-36 hours.

[0016] In the above preparation method, the inert atmosphere is an argon atmosphere.

[0017] In the above-mentioned preparation method, in step (1), the purity of the metal Ti, Zr, Mn, Fe and Bi raw materials is ≥99.9wt%, and 5wt% of metal Mn is additionally added to compensate for smelting losses.

[0018] The above 5 wt % refers to the percentage of the additional added mass of Mn to the mass of Mn in the molecular formula of the Ti—Zr—Mn—Fe—Bi hydrogen storage alloy.

[0019] Finally, the application of the above-mentioned Ti-Zr-Mn-Fe-Bi hydrogen storage alloy in hydrogen storage also falls within the protection scope of the present invention.

[0020] The Ti-Zr-Mn-Fe-Bi hydrogen storage alloy of the present invention needs to be activated before the hydrogen storage test; specifically, the activation temperature is 25° C., the activation pressure is 5 MPa, and the number of activations is 5 times.

[0021] The present invention forms a uniform phase structure by adding Zr, Mn, Fe and Bi elements to a Ti-Mn hydrogen storage alloy and optimizing the element ratio and high-temperature annealing process. While ensuring a high hydrogen storage capacity (hydrogen storage capacity ≥ 1.747wt%), the problem of large hysteresis caused by alloy element segregation is effectively reduced. The atomic radius of the Bi element is relatively large and it has strong ductility. It can buffer the microstrain and plastic deformation in the process of hydrogen absorption / desorption by expanding the size of the lattice gap, thereby stabilizing the crystal structure and improving the cycle life of the alloy in the long-term hydrogen absorption / desorption process. The hydrogen storage capacity of the prepared hydrogen storage alloy can still be maintained at 99% of the initial capacity after 2000 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The Ti prepared in Example 1 0.85 Zr 0.15 Mn 1.3 Fe 0.1 Bi 0.1 The hydrogen absorption and desorption curves for the first time and after 2000 times of hydrogen charging and discharging;

[0023] Figure 2 Ti prepared in Example 2 0.85 Zr 0.15 Mn 1.3 Fe 0.15Bi 0.05 The hydrogen absorption and desorption curves for the first time and after 2000 times of hydrogen charging and discharging;

[0024] Figure 3 Ti prepared in Example 3 0.85 Zr 0.15 Mn 1.3 Fe 0.05 Bi 0.15 The hydrogen absorption and desorption curves for the first time and after 2000 times of hydrogen charging and discharging;

[0025] Figure 4 Ti prepared in Example 4 0.85 Zr 0.15 Mn 1.4 Fe 0.05 Bi 0.05 The hydrogen absorption and desorption curves for the first time and after 2000 times of hydrogen charging and discharging;

[0026] Figure 5 Ti prepared in Comparative Example 1 0.85 Zr 0.15 Mn 15 The hydrogen absorption and desorption curves for the first time and after 2000 times of charging and discharging. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, rather than for limiting the scope of the present invention.

[0028] The experimental methods in the following examples are all conventional methods unless otherwise specified.

[0029] The quantitative tests in the following examples were all repeated three times, and the results were averaged.

[0030] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0031] Embodiment 1, Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.1 Bi 0.1 Preparation of hydrogen storage alloys

[0032] (1) According to Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.1 Bi 0.1The corresponding raw materials are weighed and mixed according to the atomic ratio of Ti, Zr, Mn, Fe and Bi, wherein the raw material purity of Ti, Zr, Mn, Fe and Bi is 99.9wt%, and 5wt% Mn raw material is additionally added to make up for the sintering loss; if calculated based on 10g, the amount of each metal is as follows: Ti 2.67g, Zr 0.90g, Mn 4.92g, Fe 0.37g, Bi 1.37g, wherein Mn has been considered to be 5wt% excessive;

[0033] (2) The mixed material obtained in step (1) is loaded into a graphite crucible of a vacuum induction melting furnace. The furnace is first evacuated to -0.1 MPa, and argon gas is introduced to -0.05 MPa. This operation is repeated three times to ensure that the furnace is in an inert gas atmosphere. The temperature is then adjusted until the alloy powder is melted. The molten metal is kept warm for 5 minutes (1800°C to 1900°C), poured into a copper mold, and cooled to form. After a single smelting, the alloy is remelted. After repeated smelting three times, an alloy ingot is obtained;

[0034] (3) The alloy ingot obtained in step (2) was placed in a quartz tube, evacuated to -0.1 MPa, and then argon gas was introduced to -0.05 MPa. The temperature was adjusted to 1200° C. and the alloy ingot was annealed for 36 h to obtain Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.1 Bi 0.1 Hydrogen storage alloys;

[0035] (4) Activating the hydrogen storage alloy obtained in step (3) and testing its hydrogen storage performance, the test method is as follows:

[0036] a. Weigh 0.1g of hydrogen storage alloy and place it in the sample chamber. Fill 0.05g of quartz wool on top of the alloy. Then put the sample chamber into the heating jacket, connect it to the air inlet pipe and tighten it. Set the temperature of the heating jacket to 25℃.

[0037] b. Enter the alloy molecular formula, sample mass, and quartz wool mass in the software, set the maximum test pressure to 5MPa, the minimum test pressure to 0.01MPa, the hydrogen absorption vacuum time to 1800s, the hydrogen absorption test time to 1800s, the number of cycles to 5 times, and then click Start Test to activate the hydrogen storage alloy by charging and dehydrating hydrogen.

[0038] c. After activation is completed, set the number of cycles to 1, and the other parameters are the same as the activation parameters. Click Start Test to obtain the first hydrogen absorption and desorption data.

[0039] d. After the first hydrogen absorption and desorption is completed, set the number of cycles to 2000 times. The other parameters are the same as the activation parameters. Click Start Test to obtain the 2000th hydrogen absorption and desorption data.

[0040] Embodiment 2, Ti0.85 Zr 0.15 Mn 1.3 Fe 0.15 Bi 0.05 Preparation of hydrogen storage alloys

[0041] (1) According to Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.15 Bi 0.05 The corresponding raw materials are weighed and mixed in an atomic ratio of 99.9 wt %, wherein the raw material purity of Ti, Zr, Mn, Fe and Bi is 99.9 wt %, and 5 wt % Mn raw material is additionally added to compensate for the sintering loss;

[0042] (2) The mixed material obtained in step (1) is loaded into a graphite crucible of a vacuum induction melting furnace, the furnace is first evacuated to -0.1 MPa, argon gas is introduced to -0.05 MPa, and this operation is repeated three times to ensure that the furnace is in an inert gas atmosphere, and then the temperature is adjusted until the alloy powder is melted, the molten metal is kept warm for 5 minutes, and poured into a copper mold for cooling and forming. After a single smelting, the alloy is remelted, and the alloy ingot is obtained after repeated smelting three times;

[0043] (3) The alloy ingot obtained in step (2) was placed in a quartz tube, and vacuumed to a gauge pressure of -0.1 MPa, and then argon was introduced to -0.05 MPa, and the temperature was adjusted to 1200° C. The alloy ingot was annealed for 36 h to obtain Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.15 Bi 0.05 Hydrogen storage alloys;

[0044] (4) The hydrogen storage alloy obtained in step (3) is activated and its hydrogen storage performance is tested, and the test method is the same as that in Example 1.

[0045] Embodiment 3, Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.05 Bi 0.15 Preparation of hydrogen storage alloys

[0046] (1) According to Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.05 Bi 0.15 The corresponding raw materials are weighed and mixed in an atomic ratio of 99.9 wt %, wherein the raw material purity of Ti, Zr, Mn, Fe and Bi is 99.9 wt %, and 5 wt % Mn raw material is additionally added to compensate for the sintering loss;

[0047] (2) The mixed material obtained in step (1) is loaded into a graphite crucible of a vacuum induction melting furnace, the furnace is first evacuated to -0.1 MPa, argon gas is introduced to -0.05 MPa, and this operation is repeated three times to ensure that the furnace is in an inert gas atmosphere, and then the temperature is adjusted until the alloy powder is melted, the molten metal is kept warm for 5 minutes, and poured into a copper mold for cooling and forming. After a single smelting, the alloy is remelted, and the alloy ingot is obtained after repeated smelting three times;

[0048] (3) The alloy ingot obtained in step (2) was placed in a quartz tube, evacuated to -0.1 MPa, and then argon gas was introduced to -0.05 MPa. The temperature was adjusted to 1200°C, and the alloy ingot was annealed for 36 hours. Ti 0.85 Zr 0.15 Mn 1.3 Fe 0.05 Bi 0.15 Hydrogen storage alloys;

[0049] (4) The hydrogen storage alloy obtained in step (3) is activated and its hydrogen storage performance is tested, and the test method is the same as that in Example 1.

[0050] Embodiment 4, Ti 0.85 Zr 0.15 Mn 1.4 Fe 0.05 Bi 0.05 Preparation of hydrogen storage alloys

[0051] (1) According to Ti 0.85 Zr 0.15 Mn 1.4 Fe 0.05 Bi 0.05 The corresponding raw materials are weighed and mixed in an atomic ratio of 99.9 wt %, wherein the raw material purity of Ti, Zr, Mn, Fe and Bi is 99.9 wt %, and 5 wt % Mn raw material is additionally added to compensate for the sintering loss;

[0052] (2) The mixed material obtained in step (1) is loaded into a graphite crucible of a vacuum induction melting furnace, the furnace is first evacuated to -0.1 MPa, argon gas is introduced to -0.05 MPa, and this operation is repeated three times to ensure that the furnace is in an inert gas atmosphere, and then the temperature is adjusted until the alloy powder is melted, the molten metal is kept warm for 5 minutes, and poured into a copper mold for cooling and forming. After a single smelting, the alloy is remelted, and the alloy ingot is obtained after repeated smelting three times;

[0053] (3) The alloy ingot obtained in step (2) was placed in a quartz tube, and vacuumed to a gauge pressure of -0.1 MPa, and then argon was introduced to -0.05 MPa, and the temperature was adjusted to 1200° C. The alloy ingot was annealed for 36 h to obtain Ti 0.85 Zr 0.15 Mn1.4 Fe 0.05 Bi 0.05 Hydrogen storage alloys;

[0054] (4) The hydrogen storage alloy obtained in step (3) is activated and its hydrogen storage performance is tested, and the test method is the same as that in Example 1.

[0055] Comparative Example 1, Ti 0.85 Zr 0.15 Mn 1.5 Alloy preparation

[0056] (1) According to Ti 0.85 Zr 0.15 Mn 1.5 The corresponding raw materials are weighed and mixed in an atomic ratio of 99.9 wt %, wherein the raw material purity of Ti, Zr and Mn is 99.9 wt %, and 5 wt % Mn raw material is additionally added to compensate for sintering loss;

[0057] (2) The mixed material obtained in step (1) is loaded into a graphite crucible of a vacuum induction melting furnace, the furnace is first evacuated to -0.1 MPa, and then argon gas is introduced to -0.05 MPa, and this operation is repeated three times to ensure that the furnace is in an inert gas atmosphere, and then the temperature is adjusted until the alloy powder is melted, the molten metal is kept warm for 5 minutes, and then poured into a copper mold for cooling and forming. After a single smelting, the alloy is remelted, and the alloy ingot is obtained after repeated smelting three times;

[0058] (3) The alloy ingot obtained in step (2) was placed in a quartz tube, and vacuumed to a gauge pressure of -0.1 MPa, and then argon was introduced to -0.05 MPa, and the temperature was adjusted to 1200° C. The alloy ingot was annealed for 36 h to obtain Ti 0.85 Zr 0.15 Mn 1.5 alloy;

[0059] (4) The hydrogen storage alloy obtained in step (3) is activated and its hydrogen storage performance is tested, and the test method is the same as that in Example 1.

[0060] Table 1 Hydrogen storage performance of the hydrogen storage alloys prepared in Examples 1-4 and Comparative Example 1 for the first hydrogen absorption and desorption and after 2000 hydrogen absorption and desorption cycles

[0061]

[0062] The hydrogen absorption and desorption curves of the alloys prepared in Examples 1-4 and Comparative Example 1 for the first time and after 2000 cycles of hydrogen charging and desorption are shown in Figure 1-Figure 5 From Table 1 and Figure 1-5It can be seen that the hydrogen storage capacity of the hydrogen storage alloys of Examples 1 to 4 is ≥1.747wt% for the first hydrogen absorption and desorption, and ≥1.740wt% after 2000 cycles of hydrogen absorption and desorption. Compared with Comparative Example 1 (the hydrogen storage capacity for the first hydrogen absorption and desorption is 1.554wt%, and the hydrogen storage capacity after 2000 cycles of hydrogen absorption and desorption is 1.141wt%), they have better hydrogen storage performance and cycle performance. The first hydrogen absorption and desorption hysteresis coefficient of Examples 1, 2 and 4 is ≤0.13, and the hysteresis coefficient after 2000 hydrogen absorption and desorption cycles is ≤ the first hydrogen absorption and desorption hysteresis coefficient ≤0.15, which is lower than that of Comparative Example 1 (the first hydrogen absorption and desorption hysteresis coefficient is 0.16, and the hysteresis coefficient after 2000 hydrogen absorption and desorption cycles is 0.19). The first hydrogen absorption and desorption hysteresis of Example 3 is 0.11, which is less than that of Comparative Example 1, and the hysteresis coefficient after 2000 hydrogen absorption and desorption cycles is 0.21, which is not much different from Comparative Example 1. Therefore, the alloy has low requirements on equipment during use and has low energy loss. Therefore, Ti 0.85 Zr 0.15 Mn 1.5-x-y Fe x Bi y The alloy has a stable hydrogen absorption and desorption process and good recycling performance, and is expected to be widely used in hydrogen storage modules of hydrogen energy equipment.

Claims

1. A Ti-Zr-Mn-Fe-Bi hydrogen storage alloy, characterized in that: The molecular formula of the Ti-Zr-Mn-Fe-Bi hydrogen storage alloy is Ti 0.85 Zr 0.15 Mn 1.5-x-y Fe x Bi y , where 0<x≤0.2, 0<y≤0.2; x and y represent the atomic ratios of Fe and Bi elements respectively.

2. The method for preparing the Ti-Zr-Mn-Fe-Bi hydrogen storage alloy according to claim 1, characterized in that: The steps include: (1) preparing Ti, Zr, Mn, Fe and Bi raw materials according to the molecular formula of the Ti-Zr-Mn-Fe-Bi hydrogen storage alloy; (2) melting and keeping the mixture in an inert atmosphere, then remelting, and obtaining an alloy ingot after repeated smelting; (3) Annealing the alloy ingot obtained in step (2) in an inert atmosphere to obtain the Ti—Zr—Mn—Fe—Bi hydrogen storage alloy.

3. The preparation method according to claim 2, characterized in that: In step (2), the temperature of the melting and heat preservation is 1700-1900° C.; The melting and heat preservation time is 3 to 5 minutes; The number of repeated smelting is 3 to 5 times.

4. The preparation method according to claim 2, characterized in that: In step (3), the annealing temperature is 1000-1200° C.; the annealing time is 24-36 hours.

5. The preparation method according to claim 2, characterized in that: The inert atmosphere is an argon atmosphere.

6. The preparation method according to claim 2, characterized in that: In step (1), the purity of the metal Ti, Zr, Mn, Fe and Bi raw materials is ≥99.9wt%, and 5wt% of metal Mn is additionally added to compensate for smelting losses.

7. Use of the Ti-Zr-Mn-Fe-Bi hydrogen storage alloy according to claim 1 in hydrogen storage.